(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
Divination reports are very important documentation for the study of the role and significance of ancient prophecy. They are also an invaluable source in the reconstruction of historical events. The object of this paper is to show how the reconstruction of the chronology and course of events based on divination reports, while using other texts written on clay tablets, becomes more complete and distinct.